Safety of concurrent adjuvant radiotherapy and chemotherapy for locally advanced soft tissue sarcoma. Issue 5 (October 2018) - Greto, Daniela; Loi, Mauro; Saieva, Calogero; Muntoni, Cristina; Delli Paoli, Camilla; Becherini, Carlotta; Ciabatti, Cinzia; Perna, Marco; Campanacci, Domenico; Terziani, Francesca; Beltrami, Giovanni; Scoccianti, Guido; et al.
Introduction: This retrospective study analyzes the safety and feasibility of concurrent chemoradiotherapy (CRT) in adjuvant treatment of soft tissue sarcoma (STS). Methods: A total of 158 patients with STS were retrospectively analyzed. Anthracycline-based computed tomography was performed in high-risk patients. Acute radiotherapy toxicity and chemotherapy-related toxicity were assessed according to the Common Terminology Criteria for Adverse Events 4.0; late radiotherapy toxicity was recorded according to Radiation Therapy Oncology Group/European Organization for Research and Treatment of Cancer criteria. Results: Fifty-four (34.2%) patients received CRT. Mean follow up was 5.4 years (range .2–21.1 years). Local DFS–recurrence-free survival, distant DFS–relapse-free survival, and overall survival were 79.1%, 76.4%, and 64.6%, respectively, at last follow-up. Leukopenia occurred in 11.4% of patients. Skin acute toxicity developed in 60.1% of patients and determined interruption of radiotherapy treatment in 19 (12%) patients. Nineteen patients (12%) experienced moderate fibrosis (grade 2). Mild and moderate joint stiffness was recorded in 16 (10.1%) patients. Size ≥5 cm was the only predictor of local recurrence at multivariate analysis (hazard ratio [HR] 9.65, 95% confidence interval [CI] 1.28–72.83, p = .028). Age and stage resulted as independent distant relapse predictors (HR 4.77, 95% CI 1.81–12.58, p = .002 and HR 4.83, CI 1.41–16.57, p = .012, respectively). At Cox regression univariate analysis, Karnofsky Performance Status, size, and stage were significant survival predictors (HR 2.23, 95% CI 1.02–4.87, p = .045; HR 2.88, 95% CI 1.10–7.52, p = .031; HR 2.59, 95% CI 1.11–6.04, p = .028). Conclusions: Concurrent CRT is a well-tolerated treatment option with no additional toxicity compared to exclusive radiotherapy or sequential CRT.